PRODUKSI ASAM HIALURONAT OLEH Streptococcus zooepidemicus DENGAN KULTIVASI CURAH (BATCH) DAN SEMI-SINAMBUNG (FED-BATCH) PADA FERMENTOR SKALA MENENGAH (10 L) - Erliza Noor Dept. TIN (Jurnal Teknologi Industri Pertanian, 2006)
ABSTRACTHyaluronic acid is a major macromolecule component of the intercellular matrix of most connective tissues such as joint fluid, vitreous, cord etc. This acid can also be obtained from microorganisms, e.g. the Streptococcus bacteria.  As a continuation of a prior research conducted on small scale, the objective of the research was to produce hyaluronic acid from Streptococcus zooepidemicus on a medium scale fermentor (10 L) and to observe the possibility to reduce the utilization of Na2HPO4.2H2O if compared to formerly conducted research (28 g/L). From the three concentrations observed, the natrium phosphate salt consumption of 14 g/L was more favorable financially.  Production of hyaluronic acid on a medium scale involved batch and fed-batch wise cultivation at an optimum process condition.  Results revealed that fed-batch cultivation increased the yield of hyaluronic acid up to 72 % if compared to batch cultivation with better hyaluronic acid pureness, i.e. 55 %. A significant impact induced by both cultivations were its cultivation time wherein that duration of fed-batch was longer than batch cultivation, consequently producing higher cell and biomass concentrations.Key words: hyaluronic acid, batch/ fed-batch cultivation